2019
DOI: 10.1159/000502962
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Subjective Characteristics of Vigilance under Different Narrow-Bandwidth Light Conditions: Do Shorter Wavelengths Have an Alertness-Enhancing Effect?

Abstract: The aim of this study was to explore the effects of 20 min of narrow-bandwidth light exposure of different wavelengths (455, 508, and 629 nm, with irradiance of 14 µW/cm<sup>2</sup>) on various neuropsychological and neurophysiological parameters of vigilance in healthy volunteers and to provide further evidence of the behavioral (subjective sleepiness, reaction time) and electrophysiological (P300 and spectral characteristics) responses to light. The results show that the short-wavelength light co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…28 Interestingly, Smotek and coworkers reported an alerting effect for selected variables after exposure to a shortwavelength (blue) light. 29 Further, increased body temperature and heart rate have also been documented after exposure to shortwavelength light (460 nm). 30 These non-image forming effects are believed to be mediated by intrinsically photosensitive retinal ganglion cells (ipRGCs) with particular sensitivity to blue light spectrum from 460 to 480 nm wavelength.…”
Section: Cognitive-behavioral Therapy For Insomniamentioning
confidence: 99%
See 1 more Smart Citation
“…28 Interestingly, Smotek and coworkers reported an alerting effect for selected variables after exposure to a shortwavelength (blue) light. 29 Further, increased body temperature and heart rate have also been documented after exposure to shortwavelength light (460 nm). 30 These non-image forming effects are believed to be mediated by intrinsically photosensitive retinal ganglion cells (ipRGCs) with particular sensitivity to blue light spectrum from 460 to 480 nm wavelength.…”
Section: Cognitive-behavioral Therapy For Insomniamentioning
confidence: 99%
“…The wavelengths in the blue part of the spectrum (400‐490 nm) significantly suppress melatonin secretion 28 . Interestingly, Smotek and coworkers reported an alerting effect for selected variables after exposure to a short‐wavelength (blue) light 29 . Further, increased body temperature and heart rate have also been documented after exposure to short‐wavelength light (460 nm) 30 .…”
Section: Non‐pharmacologic Therapiesmentioning
confidence: 99%
“…Baek et al [38] found that blue light (short wavelength) significantly reduced EEG alpha activity but increased work productivity after lunch. Michal et al [39] confirmed that short-wavelength light could enhance cognitive efficiency in task-specific scenarios. Eroglu et al [40] proposed that the types and luminance of visual stimuli can be revealed by changing the activity power of the brain.…”
Section: Introduction 1background and Literature Reviewmentioning
confidence: 96%
“…Šmotek et al [61] compared the alerting effects of 455 nm, 508 nm and 629 nm at identical irradiance (14 µW/cm²) but different illuminance (Table 3) against dim light. The investigation took place in the afternoon and lasted 20 minutes.…”
Section: First Authormentioning
confidence: 99%